Early percutaneous dilational tracheostomy does not lead to an increased risk of surgical site infection following anterior spinal surgery. Issue 2 (February 2017) - Kaczmarek, Chris; Aach, Mirko; Hoffmann, Martin F.; Yilmaz, Emre; Waydhas, Christian; Schildhauer, Thomas A.; Hamsen, Uwe
Abstract : BACKGROUND: Most patients with cervical spinal cord injuries require tracheostomy. The optimal timing is still a matter of debate. Previous studies showed that patients receiving early tracheostomy had fewer ventilator days and decreased rates of pneumonia and were mobilized earlier. Because of the proximity of the anterior approach to the tracheostoma, there is concern about an increased risk of surgical site infection (SSI) related to tracheostomy. METHODS: This was a retrospective analysis at a Level I trauma center of patient records from 2008 to 2014, identifying all patients with spinal cord injury who received anterior cervical spinal surgery and had early percutaneous dilational tracheostomy (PDT). Follow-up for SSI was performed throughout hospital stay (mean, 110 days; median, 96 days, with lower quartile 89 days and upper quartile 119 days) and at 6 weeks and 3 months (clinical examination and computed tomography scans). RESULTS: Fifty-one patients underwent anterior spinal surgery with PDT performed within a median of 5 days (range, 1–18 days). Seventy-eight percent (n = 40) of patients had anterior spinal surgery, whereas 22% (n = 11) had a combined anterior-posterior repair. All percutaneous dilational tracheostomies were performed using the Ciaglia single-step dilation technique. Despite an SSI of one patient's cannulation site, no SSI of the anterior approach was observed. CONCLUSION: Performing a PDT in a timely fashion after anterior spinal surgery does not increase the risk of SSI. LEVEL OF EVIDENCE: Therapeutic study, level V.